True love - Deveraux, Jude; Deveraux, Jude (New York : Ballantine Books, 2013)
After she mysteriously inherits a nineteenth-century Nantucket house, Alix Madsen gets drawn into the unsolved disappearance of her ancestor two hundred years ago and begins to have feelings for Jared Montgomery, who lives in the property's guesthouse.
"This Large Print Edition, prepared especially for Doubleday Large Print Home Library, contains the complete, unabridged text of the original Publisher's Edition." -- T.p. verso.
100536
Keywords: Man-woman relationships; Weddings -- Planning; Large type books; Nantucket Island (Mass.); Love stories